(untitled) (Estima – Brazilian Journal of Enterostomal Therapy, 2020)
Objective: To compare the cost of dressing with the use of conventional and advanced dressings in Primary Health Care. Method: Retrospective longitudinal study conducted in a municipality in the interior of Minas Gerais, Brazil, which followed 15 patients from admission to the healing of skin lesions to calculate treatment costs. Previous treatment up to the time of admission to the study was compared by processing the time and materials spent with the current treatment with advanced coverage. Results: In the conventional treatment, the average time of existence of the lesion before admission in the study was 620 days. The estimated total cost of all patients with daily change of conventional dressing was R 101,030.58 (US 26,586.94). In the advanced coverage treatment modality, the average follow-up time was 151 days, resulting in a total cost of R 15,631.02 (US 4,113.43). The savings were over R 85,000.00 (US 22,370.00). Conclusion: The cost of treatment with advanced coverages was seven times lower for the municipality, in addition to reducing the healing time for patients, allowing a shorter return to their work activities.